Impact of interest rate surprises on Islamic and conventional stocks and bonds. (December 2017) - Akhtar, Shumi; Akhtar, Farida; Jahromi, Maria; John, Kose
Highlights: We are first to show interest rate news surprise (IRS) comparison on Islamic assets. We are first to document interest rate news surprise on an international setting. IRS have smaller impact on the returns/volatility of Islamic than non-Islamic bonds. IRS has at least same impact on the returns/volatility of Islamic stocks. IRS impacts on Islamic and non-Islamic assets vary across countries. Abstract: This paper studies the impact of interest rate news surprises on Islamic and conventional stock and bond indices, using a dataset which covers interest rate announcements and forecasts, as well as stock and bond indices in three Islamic and eight non-Islamic countris. We find that interest rate surprises tend to have a smaller impact on the returns and volatility of Islamic than conventional bonds because Islamic bonds are structured to avoid explicit interest rates. However, interest rate surprises have about the same or bigger impact on the returns and volatility of Islamic relative to conventional stocks, despite the low amounts of cash and debt holdings of firms comprising Islamic stock indices.